Exploring the Role of AI and IoT in Production Efficiency, Quality, and Sustainability in Manufacturing - Mustafa M. Mansour; Alaa M. Lafta; Azhar Mansoor Salman; Haider Sami Salman (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
This study explores the findings obtained through these research objectives, which will pave new agendas towards the medium-range economy renaissance, resilient digital ecosystems, and human-centered integrated intelligence. More in-depth exploration of the goal-specific research objectives awaits the research report. The main research gap and questions – and concomitant research approach, paradigm, and methodologies – framing the subsequent sections of the paper are substantiated by these objectives' delineation from the research questions. Practical implications and directions for prospective areas of techno-social innovation studies, building upon the findings, are outlined to conclude the paper. The aims, once accomplished, offer a symbiotic relationship with the research questions that catalyze interest in a domain that has hitherto been neglected mainly in Industry 4.0 literature. These aims become the guiding lights surmounting the destination of AIoT as a subversive innovation in developing and deploying discrete, reconfigurable, and near-continuous Industry 4.0 auxiliary open smart manufacturing.